Advances in non-apoptotic regulated cell death: implications for malignant tumor treatment - Zhang, Yizheng; Yi, Shiqi; Luan, Mingyuan (Frontiers in Oncology, 2025)
Cell death mechanisms are broadly classified into accidental cell death (ACD) and regulated cell death (RCD). ACD such as necrosis, is an uncontrolled, accidental process, while RCD is tightly regulated by specific signaling pathways and molecular mechanisms. Tumor cells are characterized by their ability to evade cell death and sustain uncontrolled proliferation. The failure of programmed cell death is a key contributor to tumor initiation, progression, and resistance to cancer therapies. Traditionally, research has focused primarily on apoptosis as the dominant form of RCD in cancer. However, emerging evidence highlights the importance of other non-apoptotic forms of RCD, such as pyroptosis, ferroptosis, necroptosis, and parthanatos, in tumorigenesis and treatment response. These pathways are gaining attention for their potential roles in overcoming therapy resistance. In this review, we will discuss the recent advances in the study of non-apoptotic cell death pathways in malignant tumors and explore their therapeutic implications, offering insights into new targets for cancer treatment strategies.